(untitled) (Journal of Agricultural Engineering, 2019)
The increasing demand of Cassava for our dietary needs and shortage experienced going by the burgeoning global population is a cause for concern that requires urgent attention. The study therefore considered the effect of some selected soil properties, nutrients, moisture content, yield and consumptive water use on two selected Cassava varieties TMS 0581 and TME 419 respectively. The design was a randomised complete block design of four treatments and three replicates. Treatment A had fertigation, B used poultry manure, C employed nitrogen-phosphorus-potassium, 15-15-15 while D with no treatment was used as control. Soil properties such as bulk density, particle density, soil classification and nutrients such as cation exchange capacity, organic matter, nitrogen, potassium and others were determined using standard procedures. Penman-Monteith model was used in estimating reference evapotranspiration while its product with crop coefficient produced crop evapotranspiration. Moisture content was measured at depths 10, 20 and 30 cm respectively while water use efficiency (WUE), irrigation water applied and tuber yield were also determined. The findings of this study showed that all the soil properties were within permissible levels to encourage optimum agronomic development of Cassava plant and the class was entirely a loamy soil, which permits well-developed root-tuber configuration. Tuber yields varied from 21.96 kg to 25.13 kg for TMS 0581 variety while TME 419 had 17.04 kg to 31.63 kg in all the treatments. Deficiencies were observed in some of the nutrients, which were replenished with the introduction of the fertilisers among the plots. Moisture content at 30 cm depth is suggestive of adequate water availability sufficient enough to encourage proper tuber development for optimum yield while fertigation technique was adjudged the best as it improved Cassava Tuberisation and WUE in all the treatments considered.